IMPROVING STUDENTS’ ENGLISH PRONUNCIATION SKILL THROUGH AUDIO-LINGUAL METHOD - Yani Octafia (LPPM Universitas PGRI Jombang, 2025)
This research aims to find and analyze the difficulties in English pronunciation English on students of English department. In improving the variety of English teaching methods, especially learning methods that can encourage students to improve their ability to pronounce every word in English fluently in order to create effective communication situations. The writer used the descriptive qualitative method. The participant of this research was second semester students of English Department of Universitas Pamulang in the Academic Year 2024/2025. There were 10 respondents chosen randomly. The data of this research were taken from written test through pre test and post test about identifying phonemic consonants and symbols in English Words by giving test. The writer used 40 tests to analyze by students. Moreover, the writer only focused on analyzing the statement sentences The Audio-Lingual (AL) approach is a method of learning English that focuses on developing speaking and listening skills. The techniques used in the audio-lingual approach are: Focus on pronunciation, use of audio, and drills and exercises.